2021
DOI: 10.3390/nu13051497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Selenium Status by Age and Gender: A Retrospective Observational Cohort Study in Western Romania

Abstract: Selenium, residing in a series of selenoproteins, plays an important role in both female and male reproductive function. Of particular significance for reproduction is the antioxidant glutathione peroxidase (GPx), a main selenoenzyme, whose level is regulated by the availability of Se in the body. We hypothesized that changes in Se status, closely related to GPx activity, would result in an increased risk of reproductive dysfunction in individuals. We retrospectively investigated the serum selenium (SeS) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
0
6
1
Order By: Relevance
“…From a physiological perspective, selenium uptake may represent a primary modifiable factor that may account for differential susceptibility to stroke and infection. The optimal concentration levels in adult human blood serum are 80 to 120 mcg/L, though there is a great variety of normal values from country to country [ 14 , 115 ]. However, selenium concentration is age dependent [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a physiological perspective, selenium uptake may represent a primary modifiable factor that may account for differential susceptibility to stroke and infection. The optimal concentration levels in adult human blood serum are 80 to 120 mcg/L, though there is a great variety of normal values from country to country [ 14 , 115 ]. However, selenium concentration is age dependent [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, absorption of selenocompounds by the intestinal epithelia seems to be greater in females (~96%) [ 120 ] compared to males (~76%) [ 121 ]. A recent study in western Romania found that selenium uptake was lower in females compared to males [ 115 ]. Although these studies cannot provide a mechanism for these differences, they nevertheless should be taken into account when interpreting data and designing future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pursuant to a collaboration agreement with “Victor Babeș” University of Medicine and Pharmacy from Timișoara, Bioclinica provided services for the analysis of microelements from human fluids. Se analyses were performed using an inductively coupled plasma mass spectrometry (ICP-MS) method, as described elsewhere ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, among biomarkers used to assess Se status, blood and urine Se easily translate into use in neonate clinical settings. Blood contains almost half of the body's selenium, and blood Se concentration properly reflects Se intake or exposure; whole blood and erythrocyte Se reflect long-term status, while the serum/plasma Se (SeS) indicates short-term status ( 32 , 33 ). Urine, on the other hand, is the main route of Se excretion ( 34 , 35 ) with a selenosugar (1 β -methylseleno-N-acetyl-D-galactosamine) being the predominant speciation ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the metabolic and physiological functions, including excretion function, of older adults are gradually impaired during the aging process ( 20 , 21 ). Therefore, compared with other age groups, older adults have higher selenium levels and more cases of high selenium ( 22 24 ). Moreover, aging adults experience multisystem functional impairment and increasing susceptibility to multiple chronic diseases ( 25 ).…”
Section: Introductionmentioning
confidence: 99%